O Programa Mais Educação: um estudo da oferta de educação no contraturno escolar no município de Maceió - Santos, Vanessa Sátiro dos (2017)
This paper investigates the program Mais Educação as a public policy of induction of Educaçao Integral (Integral Education). The creation of this program makes part of a process of rearrangement in the role of Brazilian State, which inception happened in the government of Fernando Henrique Cardoso and continued in the governments of Luís Inácio Lula da Silva (2003-2011) and Dilma Rousseff (2012-2016). The aim of this research is to analyze the conception of integral education that substantiates the program Mais Educação in Maceió, reflecting on its possible contradictions when it comes to the proposition of a integral education experience. To understand this program, we will investigate the conceptions that support it in a national sphere using the documentary analysis. Through the interview with people who experienced the program, we will also learn and appropriate the founding elements in a local level, in the city of Maceió/Alagoas. We chose the Dialectical Historical Materialism as the investigating methodology and as comprehension of the reality. The research is divided in 5 moments: 1) literature review; 2) documental survey; 3) semi-structured interviews with professionals of the Education Department (Secretaria Municipal de Educação - SEMED), working in the program Mais Educação of Maceió, as well as coordinators and monitors from the attending schools; 4) organization, categorization and treatment of the data (documents and interview); 5) data analyses. This investigation intends to contribute to the public policies study in education, as well as to the debate over the integral education policies, aiming the human emancipation. We consider that the program Mais Educação put on the agenda the debate related to the Integral education again. We present some limits regarding the construction of an effectively democratic education, as the PMEd substantiates itself in compensatory policies, while proposes itself to offer new educational opportunities to children and teenagers. However, we need to highlight that it is necessary to rethink the overcoming of shift school ensuring the access to knowledge by all the students at school, considering that the right to education is the fundamental condition to the construction of an emancipated society.